Organic Photoredox‐Catalyzed 1,2‐Hydrogen Atom Transfer Enables the Synthesis of Cyclopropanes via Radical‐Polar Crossover Cyclization Cascade - Tian, Zeyu; He, Dongqin; Liang, Jun; Liu, Qing; Ye, Meiling; Hai, Li; Lv, Guanghui; Wu, Yong (Advanced synthesis & catalysis, 2025)
Cyclopropane is a prevalent synthetic building block present in pharmaceuticals and natural products, becoming a significant dimension for exploration in the fields of medicinal chemistry. However, the current synthesis methods for cyclopropane face numerous environmental and practical challenges, emphasizing the necessity of constructing more sustainable protocols. Herein, an organic photoredox‐catalyzed radical‐polar crossover cyclization cascade protocol for the synthesis of cyclopropanes enabled by 1,2‐hydrogen atom transfer is disclosed, which is distinguished by mild conditions, a broad range of substrates. Besides, drug molecules compatibility, scale‐up experiment, and synthetic transformations are performed to prove the potential application value of this protocol.